Contribution to knowledge of the oribatid mite genus Symbioribates (Acari, Oribatida, Symbioribatidae), with descriptions of two new arboreal species from Vietnam - Ermilov, Sergey G.; Salavatulin, Vladimir M.; Kolesnikov, Vasiliy B. (Zootaxa, 2023)
The family Symbioribatidae is recorded in Vietnam for the first time. Two new arboreal species of Symbioribates—S. bimorphus sp. nov. and S. tripartitus sp. nov.—are described, based on adults (males and females) collected from tree branches of Dipterocarpus alatus in Cat Tien National Park, Vietnam; the former species is sexually dimorphic, the latter species is the first non-sexually dimorphic representative within the genus. The generic diagnosis is presented. An identification key, distribution and habitats to the known representatives of Symbioribates are provided.